The Portrayal of Deaf Character in the Children's Book Entitled Dancing to the Beat (2021) - Nisrina Salma Raniahwati (Passage: Journal of English Language and Literature, 2023)
Researchers have analyzed the portrayal of characters with disabilities in children’s and adolescent literature. However, studies examining the portrayal of deaf character in children book is extremely limited, despite an increased inclusion of deaf characters in children’s literature over the past two decades (Golos Moses, 2011). The present study analyzes the portrayal of deaf character and the way meanings are constructed in children’s picture book entitled Dancing to the Beat (2021). The study employed a qualitative approach and was framed by theory of characterization (Reams, 2015). In addition, visual grammar (Kress and Leeuwen, 2006) and Cerrato’s (2012) meaning of colors are applied to analyze the visual text. The results indicate that the deaf character is portrayed through highlighting Deaf culture instead of medical impairment model. From fifteen pages analyzed, there are eleven pages which belong to Deaf culture and four pages to medical impairment. Thus, Deaf culture characteristics appeared more frequent than the medical impairment as it can be seen through her environment’s acceptance. The deaf character showed as a positive role model with self-confidence, optimism, enthusiasm and hard work through her behavior in facing her challenges. In addition, the book highlighted the importance of the role of adult and peer in deafness environment and inclusive education.